Monografía de compilación: Las subjetividades juveniles y expresiones estudiantiles en contextos escolares latinoamericanos - Moratho Núñez, Stephany (Universidad Antonio Nariño, 2021)
In this compilation monograph, juvenile subjectivities and their different expressions in Latin American school contexts were addressed. Categories such as incidence and conflict emerged from the adultcentric knowledge present in the family and school, but also the processes of resistance in defense of their youth identities.